Analysis ICT Effect on Indonesian Exports With Emerging Market Countries - Putri, Rinanda Dwirintha; Hayati, Banatul (AFEBI Economic and Finance Review, 2021)
The development of information and communication technology (ICT) has recently affected international trade besides macroeconomic variables. This study aims to analyze the influence of ICTs (internet users, mobile cellular subscriptions, and fixed telephone subscriptions) and macroeconomic variables (population, economic distance, real GDP per capita, and real exchange rate) on Indonesian export performance with 6 countries emerging markets. This study uses secondary data sourced from UN Comtrade, International Telecommunication Union (ITU), World Bank, Distancefrom.net, and Federal Reserve Economic Data. Then, this study uses a static panel data analysis with the Ordinary Least Suares (OLS) method. The results showed that internet users had a positive and significant effect on export performance, and fixed telephone subscriptions had a negative and insignificant effect. Other results showed that the population had a positive and significant effect on export performance, the distance of the economy had a negative and significant effect on export performance, real per capita GDP had a negative and insignificant effect on export performance, and the real exchange rate had a negative and significant effect on export performance. Keywords: emerging markets, export performance, ICT, macroeconomic variables, OLS methods.